1987
DOI: 10.2355/tetsutohagane1955.73.6_715
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbon and Nitrogen on the Tensile Deformation Behavior of SUS304 and 316 Stainless Steels at Cryogenic Temperatures

Abstract: Effects of C and N contents on the tensile properties and deformation behaviors at low temperatures have been investigated to obtain an alloy design basis on SUS 304 and 316 austenitic stainless steels for cryogenic application.Increase in C and N contents led to the increase in temperature dependency of 0.2% yield strength for both SUS 304 and 316 steels. However, SUS 316 steel showed larger temperature dependency than SUS 304 at the same level of (C+N) content, probably due to the solution strengthening effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…However, the 0.2% proof stress of SUS301L increased with a decrease in temperature. This may be related to the effect of nitrogen (N) on tensile properties 29,30) because the SUS301L contains N content of 0.127 mass%. Miura et al 29) investigated the effects of N and carbon (C) content on the deformation behavior at low temperatures using SUS304 and SUS316 steels.…”
Section: Effects Of Temperature and Strain Rate On Tensilementioning
confidence: 99%
See 2 more Smart Citations
“…However, the 0.2% proof stress of SUS301L increased with a decrease in temperature. This may be related to the effect of nitrogen (N) on tensile properties 29,30) because the SUS301L contains N content of 0.127 mass%. Miura et al 29) investigated the effects of N and carbon (C) content on the deformation behavior at low temperatures using SUS304 and SUS316 steels.…”
Section: Effects Of Temperature and Strain Rate On Tensilementioning
confidence: 99%
“…This may be related to the effect of nitrogen (N) on tensile properties 29,30) because the SUS301L contains N content of 0.127 mass%. Miura et al 29) investigated the effects of N and carbon (C) content on the deformation behavior at low temperatures using SUS304 and SUS316 steels. The effect of temperature on 0.2% proof stress in the SUS304 with N content of 0.128 mass% 29) agreed well with that of the SUS301L.…”
Section: Effects Of Temperature and Strain Rate On Tensilementioning
confidence: 99%
See 1 more Smart Citation
“…Miura et al suggested a method to determine the strain E MS at which DIMT may start, when fitting the true stress-true strain curve [21]. Considering that their deformation test was conducted at 77 K, the sigmoidal, two-step hardening behavior was evident.…”
Section: Analysis Of Stress-strain Curvementioning
confidence: 99%
“…Although the formation of ε martensite by DIMT is well-known, it has rarely been investigated from an engineering aspect [2]. Several researchers have extensively investigated the relationship between the α' martensite fraction and the mechanical properties of steel, particularly, the strain-hardening rate [2,3]. However, to achieve the desired mechanical properties in steel by controlling its chemical composition and/or microstructure, it is necessary to understand the effects of the γ→ε→α' and γ→α' DIMT mechanisms on the deformation of steel.…”
Section: Introductionmentioning
confidence: 99%